(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Suicide is a complex and multicausal phenomenon that occurs in all regions of the world and defies modern societies because it is an avoidable death. Objectives: To analyze the temporal trend of suicide mortality in the state of ES from 2007 to 2016. Methods: Time-series ecological study whose population comprised the deaths of 10 years or more by suicide in the health regions of ES, from 2007 to 2016, based on the Mortality Information System. Descriptive statistics were performed and polynomial regression models were estimated for suicide trend analysis. Results: A total of 1,630 suicide deaths were reported in Espírito Santo in the analyzed period. The model that represented the trend of death by suicide was second order (p <0.007) increase in the rate from 2007 to 2012 and decrease from 2013 onwards. The health regions with decreasing trends in the last five years were Metropolitana (p<0.002) and Sul (p<0.020). For men, the trend declined 10.4% and among women grew 15.3%. The age ranges 10-19 years (p<0.005) and 20-39 years (p<0.05) decreased in the last five years, and during the whole period there was a decline in suicide rates in the age groups of 60-79 years (p<0.007) and 80 years and over (p<0.001). Conclusion: The suicide rate in the ES, Metropolitan and South regions were increasing until the middle of the period and then decreased, higher among men, but with decreasing trend, while the female rate increased. Among the elderly there was also decline.